Development and Application of a Portable Environmental DNA Test for the Detection of Rafetus swinhoei in Viet Nam - Tracie A. Seimon; Nguyen Van Long; Minh Le; Timothy E. M. McCormack; Tham Thi Nguyen; Hanh Ngo; Nguyen Tai Thang; Thuy Hoang; Steven G. Platt; Hoang Van Ha; Nguyen Van Trong; Brian Horne; et al. (Environmental DNA)
ABSTRACT Swinhoe's (or Yangtze) giant softshell turtle (Rafetus swinhoei) is a large, critically endangered freshwater turtle and considered among the rarest species in the world. As of 2024, only two individuals have been confirmed to remain alive, one at the Suzhou Zoo in China and one in Xuan Khanh Lake, Viet Nam. The only hope for the long‐term survival of R. swinhoei is finding additional, as yet undiscovered, animals that have thus far eluded detection by traditional survey methods. In recent years, numerous studies have been published on the use of environmental DNA (eDNA) for species detection and monitoring. This method takes advantage of the persistence of DNA in the environment, such as in water, soil, and air. An organism's DNA is shed into the environment through urine, feces, and the sloughing of skin. Species‐specific quantitative polymerase chain reaction (qPCR) testing can be used to detect eDNA in samples collected from the environment. eDNA trials to detect R. swinhoei were initiated by the Asian Turtle Program and Washington State University in 2013. To expand the use of eDNA for species detection by conservationists, we developed and validated a first‐of‐its‐kind innovative point‐of‐detection (POD) qPCR platform for the rapid, onsite detection of R. swinhoei from water samples. Here we show that the portable eDNA test kit can be used for the successful detection of R. swinhoei in a large body of water and that pooling filters may be a useful strategy to reduce test costs and improve detection efficiency. Use of this test can expand the search for R. swinhoei in unexplored and understudied lakes, reservoirs, and other bodies of water where this species may be present and could inform field surveys utilizing eDNA for other threatened species that are rare in nature.